2019
DOI: 10.1177/1744629518818950
|View full text |Cite
|
Sign up to set email alerts
|

Sleep hygiene education and children with developmental disabilities: Findings from a co-design study

Abstract: This qualitative study develops a programme theory demonstrating the complexity embedded in sleep hygiene education (SHE) as an intervention to improve sleep problems in children with developmental disabilities (DD). In co-design workshops, eight parents and six sleep practitioners deliberated discussion themes developed from a thematic analysis of exploratory study data, guided by a 'trigger' podcast illuminating parents' narratives of SHE. A SHE tool underpinned by programme theory abstracted to mid-range th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…A participatory methodology was adopted which focuses on research which is collaborative in design, views participants as equal research partners and incorporates an agenda for change (Creswell, ; Reason & Bradbury, ). This exploratory study was carried out as a preliminary step of a broader experience‐based co‐design study using the King's Fund () toolkit involving parents and sleep practitioners as co‐researchers (Sutton, Huws, Huws, & Burton, ). Exploratory study findings informed the development of joint stakeholder service improvement groups to advance understanding of SHE intervention complexity to improve delivery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A participatory methodology was adopted which focuses on research which is collaborative in design, views participants as equal research partners and incorporates an agenda for change (Creswell, ; Reason & Bradbury, ). This exploratory study was carried out as a preliminary step of a broader experience‐based co‐design study using the King's Fund () toolkit involving parents and sleep practitioners as co‐researchers (Sutton, Huws, Huws, & Burton, ). Exploratory study findings informed the development of joint stakeholder service improvement groups to advance understanding of SHE intervention complexity to improve delivery.…”
Section: Methodsmentioning
confidence: 99%
“…A scoping review of SHE and children with developmental disabilities (Sutton, ) revealed limited evaluative evidence and qualitative research exploring parents’ and sleep practitioners’ experiences. Most sleep intervention studies focused on multi‐component SHE (SHE combined with other behavioural interventions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where co-production can involve public and service users for various outcomes and reasons, even outside of health care, EBCD is focused on improving health care service, emphasising designing experiences collaboratively. EBCD has been successfully applied in services for people with intellectual disabilities (ID) and vulnerable populations, caregivers and professionals to co-produce and co-design services for various outcomes (6)(7)(8). In Unwin et al (7) study, EBCD was used to collaborate with people with ID who were of ethnic minorities (Black and Asian) to develop tools to facilitate culturallysensitive communication and information sharing, service planning and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, EBCD involves creating a film from video recorded service user interviews, which service evaluators or co-designers use to promote discussion and identify areas for improvement. In an EBCD study which aimed to evaluate sleep services for children with developmental disabilities (DD) (Sutton et al, 2019) this approach was adapted by developing an audio podcast rather than visual film. Interviews with parents of children with DD and sleep problems were audio recorded and the author created an audio podcast from parent narrative accounts to stimulate quality improvement debate in an EBCD event.…”
Section: Introductionmentioning
confidence: 99%